2017
DOI: 10.1093/jisesa/iex047
|View full text |Cite
|
Sign up to set email alerts
|

Expression and RNA Interference of Ribosomal Protein L5 Gene in Nilaparvata lugens (Hemiptera: Delphacidae)

Abstract: The ribosomal proteins play important roles in the growth and development of organisms. This study aimed to explore the function of NlRPL5 (GenBank KX379234), a ribosomal protein L5 gene, in the brown planthopper Nilaparvata lugens. The open reading frame of NlRPL5 was cloned from N. lugens based on a previous transcriptome analysis. The results revealed that the open reading frame of NlRPL5 is of 900 bp, encoding 299 amino acid residues. The reverse transcription quantitative PCR results suggested that the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
(51 reference statements)
0
10
0
Order By: Relevance
“…RPL10 has also been identified as a substrate of NIK (NSP-interacting Kinase) and functions as a downstream effector of NIK1 in plant defense against viruses (Carvalho et al, 2008 ). RPL10 was also one of the genes that became significantly upregulated in treatments with Xanthomonas oryzae (Moin et al, 2016b ) and Zhu et al ( 2017 ) have reported the identification of the insect resistance properties of NlRPL5 in rice.…”
Section: Introductionmentioning
confidence: 99%
“…RPL10 has also been identified as a substrate of NIK (NSP-interacting Kinase) and functions as a downstream effector of NIK1 in plant defense against viruses (Carvalho et al, 2008 ). RPL10 was also one of the genes that became significantly upregulated in treatments with Xanthomonas oryzae (Moin et al, 2016b ) and Zhu et al ( 2017 ) have reported the identification of the insect resistance properties of NlRPL5 in rice.…”
Section: Introductionmentioning
confidence: 99%
“…This subsequently persuaded us to study the regulatory role of all the RPL genes under different external stimuli (Moin et al, 2016b ). This study led another group to identify the insect resistance roles of NlRPL5 in rice as an important responsive gene in resistance to the brown plant hopper, Nilaparvata lugens (Zhu et al, 2017 ). The objective of the present study is to ascertain whether RPS genes are stress responsive like the RPL genes (Moin et al, 2016b ).…”
Section: Introductionmentioning
confidence: 99%
“…The ribosomal proteins are essential for protein synthesis and are involved in multiple cell processes, including cell development, gene transcriptional regulation, cellular proliferation and differentiation [36,37,38]. Although LsRPL5 and LsRPL8 were shown to interact directly with RSV [39], their expression was found to be stable in our study.…”
Section: Discussionmentioning
confidence: 68%